Vasodilatory Capacity of the Cerebral Vasculature in Patients with Carotid Artery Stenosis - Bokkers, R.P.H.; Wessels, F.J.; van der Worp, H.B.; Zwanenburg, J.J.M.; Mali, W.P.Th.M.; Hendrikse, J. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Impairment of the cerebral autoregulation is an important predictor of TIA and stroke in patients with an ICA stenosis. The autoregulative status can be assessed directly by measuring the vasodilatory capacity of the cerebral arteries. The aim of our study was to investigate the vasodilatory capacity of the proximal and distal cerebral vasculature in patients with an ICA stenosis and healthy control subjects by combining MRA with an acetazolamide provocation challenge. MATERIALS AND METHODS: Fourteen functionally independent patients (mean age, 67.2 ± 8.7 years) with a symptomatic ICA stenosis and 19 healthy controls (mean age, 63.1 ± 7.2 years) were included. MRA was performed before and 20 minutes after intravenous administration of acetazolamide. The vasodilatory capacity of 11 proximal and distal cerebral vessels was assessed by measuring the increase in vessel diameter after acetazolamide. RESULTS: In the hemisphere ipsilateral to the ICA stenosis, there was no increase in diameter after acetazolamide, whereas a significant increase was measured in the contralateral hemisphere for the A1 and A2 segments of the ACA, the pericallosal artery, and the BA. A significant diameter increase was measured in all except 1 vessel of the controls. The vasodilatory capacity was significantly lower ipsilateral to the ICA stenosis compared with the A1 segment of the ACA and the P2 segment of the PCA in the controls. CONCLUSIONS: MRA combined with an acetazolamide provocation challenge can measure normal and impaired vasodilatory capacity of the cerebral vasculature. ACAanterior cerebral arteryAcomAanterior communicating arteryBAbasilar arteryCO2carbon dioxideFWHMfull width at half maximumICAinternal carotid arteryMRAMR angiographyPCAposterior cerebral arteryPcomAposterior communicating arteryTIAtransient ischemic attackTOFtime of flight